Implementasi Gaya Kepemimpinan Situasional Kepala Sekolah dalam Meningkatkan Kinerja Guru di SMA Negeri 1 Gresik - Moh Nurul Chabib; Amrozi Khamidi; Syunu Tri Hantoyo; Mochamad Nursalim; Kaniati Amalia; Ayu Wulandari (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This study examines the application of the situational leadership style by principals to enhance teacher performance at SMA Negeri 1 Gresik. The research utilized a literature review approach, involving data collection, identifying data sources, and drawing conclusions. The findings indicate that the principal's situational leadership style, encompassing dictating, selling, participation, and delegation, tends to be participative. This participatory approach enables teachers and staff to be more involved in school activities. Moreover, the principal's situational leadership style has a substantial impact on teacher performance. As a result, an improved situational leadership style from the principal can enhance teachers' effectiveness in carrying out their responsibilities. Keywords: Situational Leadership Style, Principal, Teacher Performance